Reading Strategies for Post-Pandemic Students' Reading Comprehension Skills - Brilliananda, Cindy Cindhana; Setiawan Edi Wibowo (International Journal of Elementary Education, 2023)
Reading comprehension skills are vital for students' information acquisition in elementary schools. However, the facts on the ground show that since the COVID-19 pandemic, students' reading skills have decreased, which is quite concerning. Solutions are needed to prevent reading comprehension problems in elementary schools. One way is to implement learning strategies that involve active student participation. This study aims to analyze the differences in the effect of the DRTA and PQRST strategies on students' reading comprehension skills. This research is a quasi-experimental quantitative research with a 2x2 factorial design. The data collection method used an essay test divided into a pretest and a posttest. The instrument used in collecting data is test questions. A total of 98 grade IV students were given treatment using the DRTA and PQRST strategies to test the difference in significance between the two and their effect on reading comprehension skills. Data were analyzed using the T-test. The results showed significant differences in reading comprehension skills in the group taught with the DRTA strategy and the group taught with the PQRST strategy. It was concluded that the DRTA group had a better effect. Choosing the right learning strategy can restore students' reading comprehension skills which have decreased due to the pandemic.